Treatment of infantile spasms: report of the interdisciplinary guideline committee coordinated by the German-speaking society for neuropediatrics - Tibussek, Daniel; Rating, Dietz (Neuropediatrics, 2016)
Objectives This report aims to define treatment goals, to summarize the evidence level (EL) of different treatment options for infantile spasms (IS), both in terms of efficacy and adverse effect, and to give recommendations for the management of IS. - - Methods The Cochrane and Medline (1966-July 2014) databases were searched. Literature known to the guideline working group and identified through citations was also considered. The results of previously published guidelines were taken into account in our analysis. Rating the level of evidence followed the Scottish Intercollegiate Guidelines Network. - - Recommendations If IS are suspected, electroencephalogram (EEG) should be performed within a few days and, if confirmed, treatment should be initiated immediately. Response to first-line treatments should be evaluated clinically and electroencephalographically after 14 days. - - Adrenocorticotropic hormone, corticosteroids, and vigabatrin are the first-line drugs for the treatment of IS. In children with tuberous sclerosis complex, vigabatrin is the treatment of first choice. Ketogenic diet, sulthiame, topiramate, valproate, zonisamide, and benzodiazepines can be used when first-line drugs have proved ineffective. Children refractory to drug therapy should be evaluated for epilepsy surgery, especially if focal brain lesions are present. - - Regular follow-up controls, including EEG (preferably sleep EEG) and standardized developmental assessment are recommended.
Gesehen am 04.09.2019